Non-data-aided timing recovery algorithm for MIL-STD SOQPSK - Wang, Qifeng; Huang, Benxiong; Xu, Zhengguang (Electronics letters, 2015)
The phase trajectory of military standard (MIL-STD) shaped-offset quadrature phase shift keying (SOQPSK) is analysed and the fourth-power nonlinearity and phase accumulation technology is used to eliminate the self-noise caused by symbol information. After the operation, the MIL-STD SOQPSK signal is converted into a pure tone during a symbol period and the timing offset is estimated from the initial phase of the tone. Computer simulation shows that its estimation performance is remarkably close to the modified Cramer-Rao bound and better than that of the existing non-data-aided method in terms of estimation accuracy.